Analisis Kinerja Struktur Akibat Ketidaksesuaian Posisi Kolom Dengan Metode Fema 356 - Nur Assyifa; Eko Walujodjati (Institut Teknologi Garut, 2026)
Discrepancies between the planning (shop drawings) and actual field conditions frequently occur in construction projects, potentially affecting the structural performance of buildings. In the Bekasi Mixed Use Development project, particularly on the P1 floor of the apartment building in Bekasi City, West Java, a problem was identified involving column positions that did not match the planned markings. This study aims to evaluate the impact of column position deviations on structural performance by conducting a preliminary design using finite element analysis. Modeling was carried out under both ideal and non-ideal conditions, with column displacements of 100 mm, 200 mm, and 350 mm. The study employed quantitative and descriptive methods, using linear response dynamic analysis based on FEMA 356. Structural calculations referred to SNI 1726-2019, SNI 1727-2020, and SNI 2847-2019 to ensure compliance with building safety standards.The analysis results showed that story drift under ideal conditions and with column displacements of 100 mm and 200 mm still met the allowable limits, whereas a 350 mm column displacement in the x-direction did not meet the specified maximum limit, with delta-x equal to 0.05226 m, which is greater than the maximum delta equal to 0.0492 m. Nevertheless, the structural performance level in all scenarios remained within the Immediate Occupancy (IO) category, with drift less than 1 percent, indicating that the building experienced only minor damage and could still be used without significant repairs.The findings of this study support risk mitigation in structural design due to column position deviations. Understanding the tolerance limits for column displacement can help identify potential field issues before they escalate. A more comprehensive technical solution for column displacement tolerance could be the focus of future research to enhance construction safety and efficiency.